Fault detection for modular multilevel converters based on sliding mode observer - Shao, Shuai; Wheeler, Patrick; Clare, Jon C.; Watson, Alan James (IEEE, 2013)
This letter presents a fault detection method for modular multilevel converters (MMC) which is capable of lo¬cating a faulty semiconductor switching device in the circuit. The proposed fault detection method is based on a sliding mode observer (SMO) and a switching model of a half-bridge, the approach taken is to conjecture the location of fault, modify the SMO accordingly and then compare the observed and measured states to verify, or otherwise, the assumption. This technique requires no additional measurement elements and can easily be implemented in a DSP or micro-controller. The operation and robustness of the fault detection technique are confirmed by simulation results for the fault condition of a semiconductor switching device appearing as an open-circuit.